Peran Badan Pengawas Obat dan Makanan Terhadap Peredaran Obat Tradisional di Kabupaten Merauke - Zegovia Parera; Salvadoris Pieter; Heri Hendri Fernando Mote (Musamus University, 2021)
The existence of traditional medicine has often been consumed and used by the people of Indonesia. Likewise, Ants Nest (Myrmecodia) is an endemic plant found in Papua, Indonesia. This plant is usually attached to the branches or stems of other larger plants, the stems are swollen and there are many small spaces or cavities inhabited by ants. The benefits of ant nests in Papua have long been used as traditional medicine in the interior of Papua, one of which is in Merauke Regency. Likewise with the Manis Mud, which is called the mud from Merauke, which is known to the public as a natural medicine inherited from the Marind Tribe. This mud in the local language is called ndave. The role of the Food and Drug Supervisory Agency (BPOM) in carrying out its duties, functions and authorities is solely to protect the rights of every consumer. The supervision carried out by BPOM is Pre Market (preliminary supervision carried out before a product is circulated in the community) and Post Market supervision (supervision carried out after the product is circulated in the community). The purpose of this study is to determine the role of the Food and Drug Supervisory Agency in dealing with the circulation of traditional medicines that do not yet have distribution and production permits. The type of research used is Empirical Law research, in addition to studying the law theoretically or normatively, it will also examine the law in its implementation. The results of the study show various laws and regulations, government regulations and regional regulations. It is appropriate that the drug and food supervisory agency in providing supervision over the circulation of traditional medicines that do not yet have distribution permits and production permits must be tightened and carry out routine checks in every district or city.